Cuidado desenvolvido por mães de crianças e adolescentes com necessidades de saúde especiais que residem no rural - Oliveira, Juliana Portela de (2024)
The objective of this study is to understand the daily care provided by mothers of CSHCN living in rural areas. This is a qualitative, descriptive-exploratory research, carried out with 27 mothers who are caregivers of children and adolescents with special health needs (CRIANES), who attend the health services of two Associations of Parents and Friends of Exceptional People located in two rural municipalities in the northwest region of Rio Grande do Sul. Data collection took place between October and December 2023 through sociodemographic characterization, a semi-structured interview script, the use of the Screening Instrument for children and adolescents with special health needs, and the construction of a genogram and ecomap. The corpus of the study was composed of the transcription of the interviews in Microsoft Word® Program and subsequently submitted to Inductive Thematic Analysis. The results showed that the daily care is characterized by challenges, ranging from discovering the diagnosis to accessing social and institutional support networks, which are often weakened, causing caregiver mothers to need to change their family dynamics to provide adequate care to their CRIANES child. Finally, the research revealed that the daily care provided by mothers of CSHCN living in rural areas involves a series of challenges faced by these women, highlighting the complexity of their realities and the particularities of their daily lives. In particular, it was found that the rural context imposes additional barriers to access to health services and the social support network, further increasing the burden on these caregivers.